Autonom autobiografisch: Zu Thomas Manns Die Entstehung des Doktor Faustus. - Hermann, Lukas (Arcadia -- International Journal for Literary Studies, 2020)
In its peritext, Thomas Mann's Entstehung des Doktor Faustus is described as a "Roman eines Romans". The essay reasons that this description of its genre as well as structural aspects of its composition mark it as an autobiographical text. Instead of following most studies on the Doktor Faustus, which regard the Entstehung simply as a documentary source for exposing autobiographical intricacies of Mann's novel, textual evidence for the Entstehung's autonomy is given. The analysis focuses first on the structural frame of the Entstehung in order to show Mann's central techniques of autobiographical self-stylization. In this context auto-fictional elements can also be identified. Exemplary passages from two longer sections are taken into account based on these findings. While the Doktor Faustus is a recurrent topic in these passages, it is not, by any means, the only one. Combined with varying autobiographical writing techniques, the Entstehung is thus displaying continuous independence from the Faustus. Based on these insights, future Mann studies on both works may reevaluate the role of the Entstehung for the reception of the Faustus and the status of autobiographical literature in the works of Thomas Mann.